Assessing User Perceptions of Tax Audit Desktop Applications: A Technology Acceptance Model (TAM) Perspective - Harjanto, Agus; Nuryanah, Siti (E-Jurnal Akuntansi; Vol 34 No 11 (2024), 2024)
The Directorate General of Taxes (DGT) has undertaken a digital transformation initiative by introducing the Desktop Pemeriksaan (Derik) application to enhance the effectiveness and efficiency of tax audits. This study aims to evaluate the performance of the Derik application from the perspective of its users, utilizing the Technology Acceptance Model (TAM) as the theoretical framework. A mixed-methods approach was employed, adopting a concurrent triangulation design to integrate qualitative and quantitative data, thereby providing a comprehensive understanding of user perceptions. The quantitative data were collected through a survey involving 1,859 respondents, while qualitative insights were gathered through in-depth interviews with eight informants. The interviews explored key aspects such as ease of use, perceived benefits, and challenges encountered by users. Data analysis was conducted using descriptive statistical methods for the quantitative findings and thematic analysis for the qualitative data. The results indicate that while the Derik application meets the criteria for perceived ease of use and perceived usefulness, several constraints hinder its optimal utilization. Based on user feedback, this study offers practical recommendations for improving the application’s functionality in future iterations. The findings contribute to the literature by providing actionable insights and serve as a valuable reference for DGT in advancing the development of the Derik application.